2010
DOI: 10.1590/s1517-86922010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Alterações morfométricas em músculo respiratório de ratos submetidos à imobilização de pata

Abstract: RESUMOA imobilização é um recurso frequentemente utilizado na prática clínica, sendo comum em patologias álgicas e nas fraturas. O objetivo deste estudo foi analisar a influência do processo de imobilização em músculo do sistema respiratório, o diafragma. O experimento foi efetuado com 12 ratos Wistar machos divididos em dois grupos, controle e imobilizado. O procedimento de imobilização foi realizado através de um método alternativo de imobilização por fita adesiva, sendo mantida por duas semanas. Analisouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
(6 reference statements)
1
5
0
6
Order By: Relevance
“…This indicated that there was loss and, consequently, muscle tissue atrophy, which is consistent with findings of different researchers in relation to skeletal muscle submitted to immobilization 15 . Reinforcing the results of this research, Slimani et al 16 demonstrated that gastrocnemius and tibialis anterior muscles, when immobilized, had higher percentage of muscle tropism compared to their controls and greater commitment of the gastrocnemius muscle.…”
Section: Discussionsupporting
confidence: 92%
“…This indicated that there was loss and, consequently, muscle tissue atrophy, which is consistent with findings of different researchers in relation to skeletal muscle submitted to immobilization 15 . Reinforcing the results of this research, Slimani et al 16 demonstrated that gastrocnemius and tibialis anterior muscles, when immobilized, had higher percentage of muscle tropism compared to their controls and greater commitment of the gastrocnemius muscle.…”
Section: Discussionsupporting
confidence: 92%
“…De acordo com os resultados obtidos no estudo em questão, pode-se afirmar que, o período de imobilização utilizado no mesmo foi suficiente para acarretar significativas alterações deletérias na morfometria do músculo sóleo de ratas wistar submetidas à ooforectomia e pseudo-ooforectomia, no que tange às variáveis de caráter longitudinal e transversal, tanto na comparação dentro dos grupos, quanto na comparação entre os grupos imobilizados com os dois primeiros (sem imobilização), demonstrando diferenças significativas de caráter hipotrófico para os lados imobilizados. Tais achados corroboram com os resultados obtidos em estudos anteriores 13,14 . De acordo com Willians e Goldspink 15 , a perda de sarcômeros em série nos músculos imobilizados em posição de encurtamento ocorre principalmente nas primeiras duas semanas após a imobilização.…”
Section: Discussionunclassified
“…It has been reported that long-lasting immobilization causes a decrease in functional performance and atrophy of muscles of the immobilized limb (4, 5, 10). To date no studies have examined morphological and functional changes in the nerves of immobilized muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In order to diminish the scars and ulcerations of non-mobilized limbs, adaptations of the immobilization procedures have been developed (4, 5, 10). The weights of the gastrocnemius and the soleus muscle were decreased in this study, confirming that our method promoted the expected negative trophic effects on muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation